Principles of Internet Marketing : New Tools and Methods for Web Developers - Miletsky, Jason I. (Boston, Massachusetts : Course Technology, 2010)
"Principles of Internet Marketing: New Tools and Methods for Web Developers" helps readers understand the why behind the how of Web site development. It teaches the importance of the brand and how that relates to Web site development, the reasons sites are developed, how they build an audience, and most importantly, how companies use the Web to earn revenue and build recognition among their desired market. You will learn the strategies used to drive traffic to a site, the tools that are available to keep audiences coming back (with a focus on social media tools), and the role marketing plays in the building a successful Web site.
An Overview of the Web -- Types of Web Sites -- Social Media and Social Networking Sites -- Blogging -- Web-Based Video -- Wikis, RSS, Mashups, and Virtual Worlds -- Understanding the Brand -- Planning and Developing the Site -- E-Commerce Sites -- Programs and Languages -- Driving Traffic: Marketing Strategies -- Capturing and Keeping an Audience -- Traffic Analysis and Measuring for Success -- Analyzing Site Traffic.
Includes index.
economic&political bookfair2016
Keywords: Internet marketing; Web site development